Educational Effects of Co-editing Columns for Establishing a Sustainable Society—Continuation and Development of “Toho Ecolution” Activities Under COVID-19 - TAKEUCHI, Ayano (ENVIRONMENTAL SCIENCE, 2024)
The spread of COVID-19 that began in early 2020 has restricted activities at universities, including extracurricular activities such as participating in clubs and circles and on-campus activities similar to semi-regular activities that involve with teachers. There is concern that this may lead to a lack of education related to career development. At the same time, the possibilities for education are expanding via the use of online environment. The purpose of this paper is to examine the educational effects, using the activity of co-editing a column as a case study, which was practiced by students engaged in environmental activities under COVID-19.As a result of organizing the students’ efforts, it was found that in addition to the acquisition of knowledge on environmental issues, the students were able to obtain the general skills required to promote environmental activities, such as the ability to coordinate, communicate, write, and proofread.